Secagem e desinfestação induzida por micro-ondas de castanha-do-brasil (Bertholletia excelsa H.B.K.) em protótipo monomodo - Silva, Alan Cândido da (2015)
The Brazil nut tree (Bertholletia excelsa HBK) belongs to Lecythidaceae is one of the most important extractive species Amazon. Because of its taste and feature an unparalleled nutritional composition, the Brazil nut almond has become a very popular food worldwide. For still be made of handmade fashion and in the rainy season, the management methods, transportation and processing have precarious as the measures required to meet the standards of ANVISA. The almond drying process is what is more difficult in the processing of the Brazil nut, as this step makes no warranties when the storage and transport of the same are not performed properly, so it can return to rehydrate, intensifying a process known as rancidity and making the product has high contamination by fungi producers of aflatoxins, preventing the marketing of that product for the domestic and foreign markets. The use of microwaves for drying various products among which also the food is well known and used in the facility on an industrial scale for several decades in developed countries. It is also known sterilizing effect materials subjected to the action of microwaves. The aim of this work is the study of physical and chemical characteristics, microbiological analysis and drying Brazil nut almond (Bertholletia excelsa HBK) extracted from RESEX Guariba-Roosevelt, using a single-mode prototype under Induction microwave (2, 45GHz), aiming at a more efficient drying and promoting the same step, sterilization of almonds keeping the nutraceutical characteristics of the Brazil nut, within the parameters established by ANVISA. The average particle size found for the almonds to the integument was 45,07mm X-axis and the 27,22mm Y-axis, 19,27mm in the Z-axis. As for the kernel without tegument, the average size of the 37,07mm X-axis, 17,02mm Y-axis and 13,68mm Z-axis. Quantification of external mycobiota through the CFU count was 4,35-Log in the middle AFPA Base, 4,33-Log amid Sabouraud Dextrose Agar, 4,34-Log dichloran glycerol agar and 0-Log amid Malachite Green. The quantification of the inner integument mycobiota was 90.83% for the medium AFPA Base, 100% for medium Sabouraud Dextrose Agar medium at 84.16% and 62.5% Dichloran Glycerol among Malachite Green. Since the quantification of mycobiota internal to the kernel was 64.27% among 100% Base medium Sabouraud Dextrose Agar medium at 87.50% and 21.67% Dichloran Glycerol among Malachite Green. Could the isolation of 51 fungal strains, 20 strains isolated from the outside of the tegument and 31 strains isolated from the inside of the tegument (kernel) among which, 6 lines from the outside and the inside of 7 strains have been identified by HPLC / MS, CCD and as producers of Aflatoxins. The results concerning the drying show a significant reduction of 46.4% in the moisture content and almond water activity, 2 cycles (60:60), and 120 seconds irradiation a total drying time of 4.33 minutes. The time of 120 seconds (2 cycles 60:60) of emission was enough to reduce about 81,25 % of the fungal contamination inside the almond and about 61,67 % inside the tegument, but this time of irradiation was not enough to reduce fungal contamination outside the integument, also causing the thermal degradation of the kernel. Further work is needed to increase reactor efficiency without changing the almond organoleptic characteristics.